Hematopoiesis of Indeterminate Potential and Atherothrombotic Risk - Murphy, Andrew J.; Dragoljevic, Dragana; Natarajan, Pradeep; Wang, Nan (Thrombosis and Haemostasis, 2022)
Hematopoiesis is the process of blood production, essential for the continued supply of immune cells and red blood cells. However, the proliferative nature of hematopoietic stem cells (HSCs) renders them susceptible to developing somatic mutations. HSCs carrying a mutation can gain a selective advantage over normal HSCs and result in hematological disorders. One such disorder is termed clonal hematopoiesis of indeterminate potential (CHIP), a premalignant state associated with aging, where the mutant HSCs are responsible for producing a small portion of mature immune cells in the circulation and subsequently in tissues. People with CHIP have been shown to have an increased risk of mortality due to cardiovascular disease (CVD). Why this occurs is under rigorous investigation, but the majority of the studies to date have suggested that increased atherosclerosis is due to heightened inflammatory cytokine release from mutant lesional macrophages. However, given CHIP is driven by several mutations, other hematopoietic lineages can be altered to promote CVD. In this review we explore the relationship between mutations in genes causing CHIP and atherothrombotic disorders, along with potential mechanisms of enhanced clonal outgrowth and potential therapies and strategies to slow CHIP progression.
Keywords: clonal hematopoiesis; atherothrombosis; somatic mutations